The Influence of Leadership and Organizational Culture on Employee Performance at PT. Pangan Mitra Bahtera - Adintya, Salsabila; Hia, Era Era; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to analyze the influence of leadership and organizational culture on employee performance at PT. Pangan Mitra Bahtera. This study uses a quantitative approach with a population of 35 people and a final sample of 32 respondents. Data analysis was conducted using validity tests, reliability tests, normality tests (Kolmogorov-Smirnov), and multiple linear regression analysis using SPSS V.25 software. The results of this study indicate that, partially, Leadership (X1) has a positive and significant effect on employee performance of 35.5% (t-calculated 3.883 > t-table 1.699). Organizational culture also has a positive and significant effect of 70.1% (t-calculated 8.651 > t-table 1.699). Simultaneously, leadership and organizational culture have a significant effect on employee performance with an F-calculated value of 86.858 > F-table 4.18 and a significance level of 0.000 < 0.05. The coefficient of determination value of 87.56% indicates a very strong contribution from both variables to employee performance at the company. It is concluded that strengthening leadership styles and fostering a conducive organizational culture are crucial for improving employee performance and productivity.